2005
DOI: 10.1099/mic.0.27493-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of temporally regulated and compartment-specific gene expression in sporulating cells of Bacillus subtilis

Abstract: Temporal and compartment-specific control of gene expression during sporulation in Bacillus subtilis is governed by a cascade of four RNA polymerase subunits. s F in the prespore and s E in the mother cell control early stages of development, and are replaced at later stages by s G and s K , respectively. Ultimately, a comprehensive description of the molecular mechanisms underlying spore morphogenesis requires the knowledge of all the intervening genes and their assignment to specific regulons. Here, in an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
203
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(217 citation statements)
references
References 125 publications
11
203
2
Order By: Relevance
“…Transcriptional profiling showing that the mRNA level of clsA and ywjE exhibits a s E -dependent increase by 2.1 and 11.7, respectively (Eichenberger et al, 2003), provides supporting evidence. Recent temporal profiling (Steil et al, 2005) also indicates a s G -dependent increase of ywjE. The hypothesis that the gene product of pssA is involved in CL production in spore membranes is consistent with the observation that pssA is apparently activated upon entry into the sporulation phase by s X and s W (Cao and Helmann, 2004).…”
Section: Resultssupporting
confidence: 65%
“…Transcriptional profiling showing that the mRNA level of clsA and ywjE exhibits a s E -dependent increase by 2.1 and 11.7, respectively (Eichenberger et al, 2003), provides supporting evidence. Recent temporal profiling (Steil et al, 2005) also indicates a s G -dependent increase of ywjE. The hypothesis that the gene product of pssA is involved in CL production in spore membranes is consistent with the observation that pssA is apparently activated upon entry into the sporulation phase by s X and s W (Cao and Helmann, 2004).…”
Section: Resultssupporting
confidence: 65%
“…Microarray data confirmed a similar expression pattern in B. subtilis (Steil et al, 2005;Wang et al, 2006) and in C. acetobutylicum (Jones et al, 2008). Accordingly, C. acetobutylicum mRNA transcripts of ssp genes could be verified only in total RNA samples of sporulating cells (Fig.…”
Section: Resultssupporting
confidence: 55%
“…The existence of a second GPR-like activity was suggested after the observation that B. subtilis spores lacking GPR are still able, albeit more slowly, to degrade a/b-type SASPs and to form colonies (Postemsky et al, 1978;Sanchez-Salas et al, 1992). GPR was classified as an atypical aspartic acid protease (Carroll & Setlow, 2005) and recently the yyaC gene product, which belongs to the s F regulon of B. subtilis (Steil et al, 2005;Wang et al, 2006), was suggested as a putative GPR-like enzyme based on conserved aspartic acid residues similar to GPR (Carroll, 2008). However, enzyme activity and substrate specificity of GPR were analysed only in B. megaterium and B. subtilis (Sanchez-Salas et al, 1992;Carroll & Setlow, 2005;Traag et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The first mother cell-specific transcription factor that is induced during sporulation is the alternative s factor s E (Stragier and Losick 1996;Piggot and Losick 2002). The s E regulon has been defined by transcriptional profiling (Eichenberger et al 2003;Feucht et al 2003;Steil et al 2005), and strains harboring deletions in most of the genes in the regulon have been generated (Eichenberger et al 2003). Using the criteria described above, we examined a subset of this ordered library of mutants using the fluorescent membrane fission assay of Sharp and Pogliano (1999).…”
Section: Fisb Is Required For Membrane Fission At the Last Stage Of Ementioning
confidence: 99%